High-quality multispectral bio-sensing with asymmetric all-dielectric meta-materials. (27th March 2017) - Liu, Zhengqi; Fu, Guolan; Liu, Xiaoshan; Liu, Yi; Tang, Li; Liu, Zhongmin; Liu, Guiqiang
Abstract: We propose and demonstrate a strategy for achieving high-quality bio-sensing in an asymmetric all-dielectric meta-material ( α -ADM), which can provide multispectral narrowband optical extinction with enhanced electromagnetic field and eventually paves a novel efficient sensing platform. High performance optical sensing with figure of merit (FoM) reaching 353 and spectral intensity change related FoM * exceeding 4700 is achieved in this lossless α -ADM platform, which is orders of magnitude larger than that of the metallic plasmonic sensors. In particular, due to the high sensitivity and complete extinction existed in the sharp spectrum, a remarkable spectral intensity change from a 'dark' state to a 'bright' state is obtained when the surrounding refractive index value is only varied slightly. Moreover, ultra-low detection limitation of the protein layer down to sub-nanometer thickness can be achieved. The sensing contrast ratio exceeding 34 dB is obtained for the sensor adsorbed with protein films, which suggests an ultra-high signal-to-noise ratio detection for this ultra-thin bio-molecule layer. In contrast to the traditional plasmonic sensors, these features lay a foundation for new sensing schemes based on the all-dielectric structures. The sensing performance including the spectral sensitivity and the detecting signal-to-noise ratio can hold the proposed α -ADM with applications in high-quality refractive index sensing and optical bio-sensing.